The β-glucuronidase activity of ox spleen and the assay of β-glucuronidase preparations - George T. Mills (1948)
LIVER CATALASE AND CANCER 125 3. The catalase concentration in normal rat liver extracts of equal protein content was not signifi- cantly changed, either by different protein levels in the diet or by peptone injections.It was raised, however, by serum injections.4. In confirmation of the work of Greenstein and his group (1941-3) it was found that the growth of a transplanted tumour leads to a fall of liver catalase concentration which, in extreme cases, may reach 5 % of normal.There was a very marked individual scatter even in similar stages of tumour growth.5. The catalase concentration when plotted against (body weight)/(tumour weight) was found to follow an exponential curve.6.The protein level of the diet had no significant effect on the course of the process, even in the initial stages.Serum injections had no effect on tumour- bearing rats when started 11 days after trans- plantation.When started 4 or 5 days after trans- plantation they were followed by regression of the tumour.